(untitled) (Journal of Asian Development Studies, 2013)
We examined the relationship between dividend policy and share price volatility across companies listed in the Nigerian Stock Exchange Market. 26 sampled firms across a number of sectors were selected through simple random sampling technique over a period (2004 – 2011). Our model specification captured share price volatility (P.vol) as the dependent variable, while dividend yield (Dyld) and dividend payout ratio (Payout) were the independent variable; firm size (size), long-term debt (Debt), earnings volatility (E.vol) and asset growth rate (ASGrT) were the control variables. For robustness purposes, the regression analysis was conducted using the pooled OLS and Panel EGLS. We also conducted various tests (i.e. Multicollinearity, Heteroskedasticity, Autocorrelation and Model specification tests) using Eviews 7.0. Our finding indicated that dividend yield exerts a positive and significant influence on share price volatility of firms while dividend payout exerts a negative and insignificant influence on share price volatility. We recommended therefore that companies should be consciously meticulous in their thoughts on efficient approach to maximizing the wealth of shareholders and simultaneously meeting the company’s needs to finance its investments.